CMER, an RNA encoded by human cytomegalovirus is most likely transcribed by RNA polymerase III. - Marschalek, R (1989)
Through computer analysis of a human cytomegalovirus (HCMV) genomic region, previously identified to be homologous to human genomic DNA, an element showing significant similarity to the 3'-internal control region (3'-ICR or B-block) of a eukaryotic RNA polymerase III promoter could be detected. This region-located on the EcoRI b fragment within the UL segment of the viral genome of HCMV strain AD 169-cannot be transcribed in vitro in an RNA polymerase III specific transcription system. However, this part of the viral genome is able to compete for components of the RNA polymerase III transcription complex as shown in template exclusion experiments and by gel retardation assays. Two different synthetic oligonucleotides complementary to the 3'-ICR and to nucleotides located immediately downstream of this promoter element can anneal specifically to a HCMV-encoded ribonucleic acid (termed CMER) synthesized in human foreskin fibroblasts (HFF) late in virus replication. As a consequence of identifying the transcription initiation point by primer extension analyses the position of the 5'-internal control region (5'-ICR or A-block) of the CMER gene could be uncovered. Both identified control regions (the A-block as well as the B-block) of the transcription unit exhibit significant similarities to corresponding regulatory elements of other class III genes, including virus encoded class III genes. Initiation of in vivo transcription occurs 15 nucleotides upstream of the 5'-border of the 5'-ICR and the two non-contiguous gene internal promoter elements are separated by 79 nucleotides.